WEBSITE APPLICATIONS BUDI USING POWER FRESHWATER FISHES MICROSOFT FRONTPAGE 2003 - Riny Yulidyaningrum; Marzuki, SKom, MMSI Marzuki, SKom, MMSI (Jurnal Sistem Informasi, 2006)
Media information is a means to convey a message or information that we can thank both orally and in writing and the media are often used such as newspapers, television, radio and computers. Internet is one medium of information very quickly, and has a very wide range and of course the information needed is information that is very fast, accurate and reliable keaslliannya. Budi Daya Freshwater is one of the information center that aims to facilitate freshwater fish lovers find information on freshwater fish, the application software Microsoft Frontpage 2003 so that this site more interesting.